A Systematic Review of Walking-Based Rehabilitation to Improve Functional Mobility, Balance, and Motor Strength in Stroke Patients - Giani, Maia Thalia; Hurriawati, Iceu Helmina; Asaduddin, Aiman Hilmi (Lembaga Penelitian dan Pendidikan, 2026)
Stroke is a major cause of long-term disability, often impairing gait, balance, and motor strength, thus reducing independence and quality of life. Walking-based rehabilitation is essential in post-stroke recovery, yet the comparative effectiveness of different modalities remains unclear. This review compared conventional physical therapy (CPT) with technology-assisted walking rehabilitation in improving functional mobility, balance, and lower limb strength during acute and subacute stroke phases. A comprehensive search of Scopus, PubMed, and Epistemonikos identified randomized controlled trials (RCTs) from 2021–2025 involving adults (≥18 years) with acute or subacute stroke. Studies compared robotic-assisted gait training (RAGT) or other technology-based walking therapies with CPT. Outcomes included gait function, balance, and motor strength. Risk of bias was assessed using the Joanna Briggs Institute tool. Eighteen RCTs (from 245 screened) met inclusion criteria. RAGT showed superior improvements in gait speed (12 studies), 6-Minute Walk Test (9 studies), and balance (Berg Balance Scale, 3 studies). Lower limb motor strength improved by 8–15 points on the Fugl-Meyer Assessment (6 studies). A higher proportion of RAGT patients achieved independent walking (Functional Ambulation Category ≥4: 56–73% vs. 29–53%). Two studies reported enhanced quality of life and three showed positive neuroplasticity changes. Adverse events were minor and resolved with adjustments. Technology-assisted walking rehabilitation outperforms CPT in improving gait, balance, and strength after stroke, supporting its inclusion in standard care. Further studies should explore long-term outcomes and optimal protocols.